Problem Situation and People’s Participation in Preventing the COVID-19 Outbreak in the Western Border Areas of Thailand - punnawit, chirawut; Nilkron, Paranee; Sawangsri, Chanwut (Princess of Naradhiwas University Journal, 2025)
Background and Objectives Currently, many countries around the world are facing the problem of the spread of the coronavirus disease 2019, or COVID-19, especially in the western border areas of Thailand, where the problem is severe and continuously increasing. This concern has led to the current research study, which aimed to investigate the situation, problems, and people’s participation in preventing the re-emergence of COVID-19 in the western border areas of Thailand. Methods This study employed a qualitative research approach, utilizing in-depth interviews with 42 participants and focus group discussions with 120 participants, conducted between November 2022 and November 2023. The research findings were analyzed using qualitative data analysis methods, specifically thematic analysis. Results The research findings indicated that the situation and problems in preventing the re-emergence of COVID-19 in the western border areas of Thailand consisted of three main issues: personal factors (host). It was found that 1) the people lack knowledge and understanding of preventing the re-emergence of COVID-19 in the western border areas, 2) people in the area have incorrect wisdom and beliefs, which contribute to the re-emergence of COVID-19, 3) the people lack media literacy skills to protect themselves from COVID-19, and 4) the people are not aware of self-protective behaviors against COVID-19 in the western border areas of Thailand. Regarding the causes of the disease (agent), it was found that 1) the COVID-19 virus, foreign populations, and environmental factors contributed to the issue, 2) the system for monitoring the re-emergence of COVID-19 in the area was unprepared, and 3) there was a lack of community participation in preventing and controlling the re-emergence of COVID-19 in the western border areas. Conclusion and Recommendations Providing education about attitudes and behaviors regarding the re-emergence of COVID-19 in the western border areas should utilize accessible media, such as audio broadcasts through village loudspeakers, as well as continuous screening and surveillance services from relevant agencies.